Evaluation of Continuous Infusion Vancomycin Administration in a Critically Ill Trauma Population. (June 2020) - Bissell, Brittany D.; Riggi, Gina; Morrison, Christopher
Vancomycin is a first-line antibiotic for empiric treatment of gram-positive infections in the trauma intensive care unit. When dosed intermittently, difficulties arise from trough collection and drug monitoring. The objective of this study was to evaluate time to goal vancomycin levels comparing a continuous infusion protocol when compared to standard intermittent infusion dosing. This was a retrospective cohort of patients admitted to the trauma intensive care unit between July 2011 and July 2015 receiving vancomycin for at least 48 hours. In this cohort of 150 patients, continuous infusion vancomycin had a decreased time to goal vancomycin level (2.5 vs 3.8 days, P ≤ .05) with a higher incidence of target attainment (60% vs 40%, P ≤ .05). This reflected in a decrease in average number of blood samples per patient (1 vs 3, P ≤ .05) and shorter duration of therapy (3.8 vs 6.8 days, P ≤ .05). Patients receiving continuous infusion vancomycin also experienced less nephrotoxicity (21% vs 43%, P ≤ .05). Patients in the intermittent infusion group had more missed levels and doses, with only 1 in every 3 patients receiving all intended doses on time. Vancomycin continuous infusion resulted in a decrease in time to goal therapeutic vancomycin levels, number of blood samples required, and therapy duration. Larger trials are needed to validate these outcomes in broad patient groups and to validate the clinical implication and potential cost savings of these results.